The Influence of Direct Marketing and Flash Sales on Impulse Buying on Tiktok Shop Live Streaming - Bayu Santoso; Albert Kriestian Adhi Nugraha (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of marketing strategies using direct marketing strategies and flash sale promos on online impulse buying behavior in TikTok live streaming. This study also considers the intensity of use of the TikTok application as a moderating variable. This research method uses a survey conducted online by distributing questionnaires to 150 TikTok users in Salatiga City and its surroundings. The results showed that direct marketing and flash sales have a positive effect on online impulse buying. The intensity of use of the TikTok application strengthens this influence. This research contributes to digital marketing theory and provides strategic recommendations for businesses that use TikTok as a marketing channel.